KONTRIBUSI INFRASTRUKTUR DIGITAL, KOMPETENSI GURU, DAN MEDIA PEMBELAJARAN TERHADAP EFEKTIVITAS PEMBELAJARAN JARAK JAUH (PJJ) DAN PRESTASI SISWA: PENDEKATAN PLS-SEM DI PURWAKARTA - Z, Raihan Hamdhan; M, Reksa Wijaya; Herdiansyah, Heru (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study analyzes the influence of digital technology on distance learning in Purwakarta Regency using the PLS-SEM approach. The COVID-19 pandemic has driven the adoption of distance learning with challenges such as gaps in internet access, device infrastructure, teachers' digital literacy, and learning media integration, which affect the quality of distance learning and student learning outcomes. The research objectives include identifying influential digital technology factors, analyzing relationships between variables, determining the main components using the PLS-SEM approach, and contributing to the effectiveness of distance learning. The method uses a Likert questionnaire with 15 indicators per variable (technology infrastructure, teachers' digital literacy, digital media use, distance learning quality, learning outcomes), analyzed using SEM for hypothesis testing. The findings show that the main components of variables X1-X3 significantly predict variations in Y1 and Y2, with the mediation of distance learning quality on student achievement. The research implications recommend policy interventions for infrastructure improvements, literacy training, and media design to make distance learning more inclusive and effective post-pandemic.